Two Receptor-Like Genes, Vfa1 and Vfa2, Confer Resistance to the Fungal Pathogen Venturia inaequalis Inciting Apple Scab Disease - Mickael Malnoy; Mingliang Xu; Ewa Borejsza-Wysocka; Schuyler S. Korban; Herb S. Aldwinckle (Molecular Plant-Microbe Interactions, 2008)
The Vf locus, originating from the crabapple species Malus floribunda 821, confers resistance to five races of the fungal pathogen Venturia inaequalis, the causal agent of apple scab disease. Previously, a cluster of four receptor-like genes, Vfa1, Vfa2, Vfa3, and Vfa4, was identified within the Vf locus. Because the amino-acid sequence of Vfa3 is truncated, it was deemed nonfunctional. In this study, each of the three full-length Vfa genes was introduced into a plant cloning vector, pCAMBIA2301, and used for Agrobacterium-mediated transformation of two apple cultivars, Galaxy and McIntosh, to assess functionality of these genes and to characterize their roles in resistance to V. inaequalis. Transformed apple lines carrying each of Vfa1, Vfa2, or Vfa4 were developed, analyzed for the presence of the transgene using polymerase chain reaction and Southern blotting, and assayed for resistance to apple scab following inoculation with V. inaequalis. Transformed lines expressing Vfa4 were found to be susceptible to apple scab, whereas those expressing either Vfa1 or Vfa2 exhibited partial resistance to apple scab. Based on Western blot analysis as well as microscopic analysis of plant resistance reactions, the roles of Vfa1 and Vfa2 in apple scab disease resistance response are discussed.